Hyper/neuroinflammation in COVID-19 and suicide etiopathogenesis: Hypothesis for a nefarious collision?. (May 2022) - Costanza, A.; Amerio, A.; Aguglia, A.; Serafini, G.; Amore, M.; Hasler, R.; Ambrosetti, J.; Bondolfi, G.; Sampogna, G.; Berardelli, I.; Fiorillo, A.; Pompili, M.; et al.
Abstract: Accumulating scientific and clinical evidence highlighted pathological hyperinflammation as a cardinal feature of SARS-CoV-2 infection and acute COVID-19 disease. With the emergence of long COVID-19 syndrome, several chronic health consequences, including neuropsychiatric sequelae, have gained attention from the public and medical communities. Since inflammatory mediators have also been accredited as putative biomarkers of suicidal ideations and behaviors, hyper- and neuroinflammation might share some colliding points, overlapping and being interconnected in the context of COVID-19. This review aims to provide a summary of current knowledge on the molecular and cellular mechanisms of COVID-19-associated hyper/neuroinflammation with focus on their relevance to the inflammatory hypothesis of suicide development. Subsequently, strategies to alleviate COVID-19 hyper/neuroinflammation by immunomodulatory agents (many of which at experimental stages) as well as psychopharmacologic/psychotherapeutic approaches are also mentioned. While suicide risk in COVID-19 survivors - until now little known - needs further analysis through longitudinal studies, current observations and mechanistic postulates warrant additional attention to this possibly emerging mental health concern. Highlights: Hyperinflammation is a hallmark of COVID-19 disease. Neuroinflammation is also involved in suicide pathogenesis. It is possible that the two inflammation cascades share colliding points. Hyper/neuroinflammation could be synergic in chronic neuropsychiatric sequelae, including suicide. This is relevant to COVID-19 survivors as long-term impact of the disease is unknown.